SMEs in the Republic of Serbia: The Developing Capacities - Đorđević, Dejan; Ćoćkalo, Dragan; Sajfert, Zvonko; Bogetić, Srđan (Journal of Applied Engineering Science, 2011)
Small and mid-sized enterprises (SMEs) represent one of the main generators of economic development in every market economy. In the last thirty years the SME sector has been successful all over the world, especially in newly industrialized and transitional countries. The management process in SMEs is specific because their business activities are performed in conditions of insufficient resources. The development of SMEs is one of the crucial developmental priorities in the Republic of Serbia. This paper represents a review of the developing capacities of SMEs in the Republic of Serbia.